2010
DOI: 10.1111/j.1365-3040.2010.02235.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Se‐fortified broccoli as functional food: impact of Se fertilization on S metabolism

Abstract: Selenium (Se)-fortified broccoli (Brassica oleracea var. italica) has been proposed as a functional food for cancer prevention, based on its high glucosinolate (GSL) content and capacity for Se accumulation. However, as selenate and sulphate share the initial assimilation route, Se fertilization could interfere with sulphur metabolism and plant growth. Consequently, GSL accumulation could be compromised. To evaluate these potentially adverse effects of Se fertilization, we performed a comprehensive study on sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 71 publications
(190 reference statements)
6
46
0
Order By: Relevance
“…Thus, broccoli is a good vegetable source of major mineral elements such as sodium, potassium, calcium, magnesium, chlorine, potassium and sulphur, and trace elements such as iron, zinc, copper, manganese and selenium (Se). Indeed, broccoli has the ability to accumulate high levels of Se with the majority of the seleno amino acids in the form of Se-methylselenocysteine, and this may also be an important factor in chemoprevention [25][26][27]. Health benefits of broccoli may also be enhanced due to the presence of proteins containing the essential amino acids isoleucine, leucine, lysine phenylalanine, tryptophan, methionine, valine and threonine, as well as beneficial fatty acids [28].…”
Section: Bioactive Chemicals In Broccolimentioning
confidence: 96%
“…Thus, broccoli is a good vegetable source of major mineral elements such as sodium, potassium, calcium, magnesium, chlorine, potassium and sulphur, and trace elements such as iron, zinc, copper, manganese and selenium (Se). Indeed, broccoli has the ability to accumulate high levels of Se with the majority of the seleno amino acids in the form of Se-methylselenocysteine, and this may also be an important factor in chemoprevention [25][26][27]. Health benefits of broccoli may also be enhanced due to the presence of proteins containing the essential amino acids isoleucine, leucine, lysine phenylalanine, tryptophan, methionine, valine and threonine, as well as beneficial fatty acids [28].…”
Section: Bioactive Chemicals In Broccolimentioning
confidence: 96%
“…The high-affinity sulphate transporter Sultr1;2 has been identified in Arabidopsis using selenate as analogue of sulphate (Shibagaki et al 2002) and has been shown to be a major contributor in the acquisition of selenate (El Kassis et al 2007). A selenate-induced expression of sulphate transporters has been reported in several studies (Hsu et al 2011;Takahashi et al 2000;Van Hoewyk et al 2008;Yoshimoto et al 2002).…”
Section: Selenium Phytoremediationmentioning
confidence: 97%
“…Extraction and quantitative analyses of the total GSL were performed following the method described by Hsu et al (2011) with minor modifications. Freeze-dried sample (0.05 g) was pulverized in a mortar, until a homogeneous meal was obtained.…”
Section: Total Gsl Contentmentioning
confidence: 99%